The impact of various instances of solar wind speed on the fluctuations of cosmic radiation in the solar minima (23, 24, and 25). (November 2022) - Wateed, N.M.; Motaweh, H.A.; Hanfi, M.Y.; Sayyed, M.I.; Khandaker, M.U.; Darwish, A.A.; Elshoukrofy, A.Sh.M.
Abstract: Its key role in space weather determines the importance of solar wind study. The solar wind is made up of various plasma streams with varying hydrodynamic and magnetic properties, which has been known for a long time. Because the distinction between the sorts of flows is conditional rather than absolute, there is still no widely agreed terminology, which varies according to the author. The number of these kinds as well as how they are classified is varied. We investigated data on solar wind speed and cosmic ray intensity for four stations, Apatity, Fort Smith, Hermanus, and Moscow, collected from the National Oceanic and Atmospheric Administration and neutron monitors, from 1998 to 2020 for three solar cycles (23, 24, and 25). Slow and rapid wind, as well as disturped streams, are the three basic forms of solar wind. The sluggish solar wind has a typical speed of 300–500 km per second. At speeds of 700–800 km/s, rapid solar wind is emitted. In all cases of solar wind speed, the amplitude and phase of daily variability on selected sites were investigated. The presence of the solar wind was recorded every day during the study time, with low solar wind events occurring more frequently than the rapid and disturped streams. Highlights: The importance of solar wind research is based on its critical role in space weather. The data of solar wind speed and cosmic ray intensity of three solar cycles had been analyzed. The solar wind is divided into three main types: slow, normal, and fast streams. The solar wind is permanent and the number of occurrences of the low solar wind is more frequent. The fluctuation of cosmic rays is influenced by the speed of the solar wind.